A Potential Therapeutic Role of Myoinositol in the Metabolic and Cardiovascular Profile of PCOS Iranian Women Aged between 30 and 40 Years - Saghar Salehpour; Leila Nazari; Sedighe Hoseini; Nasrin Saharkhiz; Fatemeh Ghazi; Mohammad Reza Sohrabi (International Journal of Endocrinology)
Introduction. Polycystic ovary syndrome (PCOS) is a common disorder in reproductive age. This pilot study investigated the effects of myoinositol (MI) treatment on metabolic and cardiovascular profile in PCOS women over 30 years of age. Methods. Between 2015 and 2016, 50 women with diagnosis of PCOS by the Rotterdam Criteria were included in the study. All women received MI 2 g plus 200 μg of folic acid (Inofolic, Health Parsian, Iran; twice daily) for 3 months. Baseline and 3-month serum samples were taken after an overnight fast to evaluate the insulin resistance index (HOMA-IR), fasting glucose, and the levels of triglyceride, total cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), homocysteine, systolic blood pressure, and diastolic blood pressure. Participants’ weight was measured before and after treatment and body mass index (BMI) was calculated. Results. The data showed a significant improvement in the serum level of insulin sensitivity and a reduction of cholesterol, LDL, and homocysteine after three months of treatment. Furthermore, blood pressure was significantly reduced in the treated patients. Three participants became pregnant during treatment. Conclusion. Results showed that supplementation with MI and folic acid in PCOS patients over 30 years of age could decrease the risk of cardiovascular problems by normalizing the metabolic profile.